Standardization of blood meal production process at a rendering plant using design of experiments - Morales Piñero, Juan Carlos; Clavijo, John Alexander; Rodríguez Ortiz, Edison Mauricio (Semina: Ciências Agrárias, 2021)
This research focuses on the standardization of the blood meal production process at a Colombian rendering plant through a design of experiments. Initially, 108 samples of blood meal were taken where only 23% achieved the moisture target (7.5% to 8.5%). Therefore, an analysis of the measurement system was performed using a repeatability and reproducibility (R&R) study. Results showed that 39.96% of the observed variability was caused by the measurement system that was out of control. So, it was necessary to improve the method of sampling reducing the participation of the measurement system in the variability of the process to only 3.79%. Later, several experiments were accomplished with a 2k factorial design. Each experiment consisted of a response variable (blood meal moisture), two controllable factors (drying chamber temperature and percentage of rotation of the metering screw), and an uncontrollable factor (initial blood meal moisture). Finally, experiments were carried out and validated observing that, with a drying chamber temperature of 160 Â°C and a percentage of screw rotation of 29%, more than 97% of the blood meal was according to the moisture target. In conclusion, is confirmed that the design of experiments is a tool that allows a clear path towards optimization and standardization of processes.